2020
DOI: 10.7759/cureus.11584
|View full text |Cite
|
Sign up to set email alerts
|

Large Intermuscular Lipoma Presenting as a Groin Hernia

Abstract: Lipomas are the commonest benign mesenchymal tumours, commonly seen as a subcutaneous lump. However, intermuscular lipomas are uncommon and can remain asymptomatic until they attain larger sizes. We discuss a rare case of a large symptomatic intermuscular lipoma in a 34-year-old woman who presented with acute on chronic groin pain. Clinical examination findings were consistent with an incarcerated inguinal hernia and imaging confirmed a large intermuscular lipoma of the anterior abdominal wall, the tip of whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A cross-sectional study by Parikh et al found that the Lever Sign Test was affected by hamstring muscle tension (p<0.001), posterior cruciate ligament (PCL) integrity (p<0.001), meniscal injury (p<0.001), and BMI (p<0.001) in a sample of 100 patients with suspected ACL injury [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study by Parikh et al found that the Lever Sign Test was affected by hamstring muscle tension (p<0.001), posterior cruciate ligament (PCL) integrity (p<0.001), meniscal injury (p<0.001), and BMI (p<0.001) in a sample of 100 patients with suspected ACL injury [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high incidence of lipomas in the spermatic cord is a phenomenon widely observed during herniorrhaphy interventions, commonly misclassified as true lipomas in surgical literature [1,2]. However, a more accurate analysis reveals that most of these masses represent extrusions of extraperitoneal adipose tissue in the inguinal canal.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of lipomas in the inguinal canal, identified during inguinal hernioplasty procedures, reveals notable variability in studies, spanning a wide range from 22.5% to 75%. This disparity is attributed to the interpretation of fatty masses in the inguinal canal region as "lipomas" in surgical literature [1,2]. However, it is crucial to emphasize that the majority of these occurrences are, in reality, protrusions of adipose tissue in the groin region.…”
Section: Introductionmentioning
confidence: 99%